La responsabilidad social empresarial en las industrias de curtiembres del municipio de Villapinzón, Cundinamarca - Amaya Aponte, Andrés Felipe; López López, Jairo Alexander (Universidad Antonio Nariño, 2021)
In this study, an investigation was carried out on the need to adapt Corporate Social Responsibility in the tannery industries of the municipality of Villapinzón, Cundinamarca, where some indicators that allow companies to be more competitive and to obtain better results were taken as a basis. With regard to its image and commitment to the environment and society, likewise, to be of great help to business strategic planning, after being implemented within its action or work plans.